AN ANALYSIS ON THE DIFFICULTIES LEVEL OF THREE ONLINE WRITTEN TEXTS - Giovani, Wanda (JOEEL (Journal of English Education and Literature), 2020)
This research aims to elaborate the difficulty levels of three different texts that bring the same topic. This research is a discourse analysis which was done by analyzing the lexical density, nominalization, and the finiteness of the texts. The three texts that have been analyzed were taken online from Wikipedia and two personal blogs for English research. The results show that the first text can be taken as the most complex text for high level readers, the second text for the intermediate level readers, and the third text for the elementary or low level readers. In terms of lexical density, the first text gains very high percentage which is up to 60%, this shows that the text is the most informative of all. Whereas, the second text and the third text’s lexical density are both 50%, which indicates that there are lack of contents in them.  Regarding to nominalization, the first text is still on the highest level with 12 nominalizations, the second text is on the intermediate level with 10 nominalizations, and the third text is on the lowest level, without any nominalization. The last is from the finiteness side. The first text has the lowest number of finiteness; the second text has the second highest number of finites, whereas the third text has the highest number of finites of all. This is the result of the highest number of lexical density and nominalization of the first text that decreases the frequency of sentences in it. The results of this research can be useful for online readers to decide what kind of reading materials which are suitable for their English levels.